Effect of the compliance of a femoral artery bifurcation on hemodynamic characteristics - Kim, Ho Young; Kim, EunYoung; Anayiotos, Andreas (My University, 2009)
Atherosclerosis is widely accepted as the main causative factor in the development of lower limb peripheral arterial disease (PAD). Approximately 8 million Americans is affected by the PAD. The atherosclerosis in PAD patients are frequently observed on the site at the femoral artery bifurcation.
Keywords: Bifurcation; Hemodynamics; Atherosclerosis; Diseases